Big trouble - Conti, Bill 1942- (Columbia TriStar Home Entertainment, 2003)
A pair of insurance swindlers scheme to raise cash so that they can send their sons to Yale University.
Bildformat: 1.85:1 anamorphic widescreen
Orig.: USA 1985